Administrasi Pembangunan Desa dan Penguatan Kompetensi Sumber Daya Manusia Lokal dalam Pengelolaan Dana Desa (Studi Kasus di Kabupaten Majalengka) - Siti Khumayah; Leni Leni Rohida S.Sos. Rohida; Siti Adira Kania; Nisrina Nur Alfi Laili (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2026)
The issue examined in this study concerns the utilization of village funds for rural development and the strengthening of local human resource competencies allocated annually by the central government. The purpose of this study is to identify the inhibiting and supporting factors as well as the efforts made by the village administration in managing village funds in the areas of village development and strengthening local human resources. This study uses descriptive qualitative methods with a focus on reviewing relevant literature, documents, and archives. The research findings indicate that the use of village funds for village development and strengthening the competence of local human resources in Majalengka Regency has not been fully implemented ideally according to the parameters. Village development administration still faces several challenges, including inadequate village apparatus, complicated regulations, lack of supporting infrastructure, and a village bureaucratic culture that has not completely changed. According to the study, bureaucratic administrative reform at the village level must be carried out in order to improve the capabilities of local human resources through continuous training, increased supervision and transparency, and optimization of the digital village administration system as strategic measures.